Incentives to Acquire Information under Mandatory versus Voluntary Disclosure - Urs Schweizer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper compares the incentives of a party to acquire information prior to negotiating contractual terms with a second party. Two legal regimes are compared: disclosing information before negotiations start is mandatory or it remains voluntary. By assumption, information can only truthfully be disclosed but, under voluntary disclosure, the fact that no evidence was found cannot credibly be communicated. If the party that may acquire information enjoys encompassing bargaining power, the incentives to acquire information will be excessive relative to first best quite generally. Otherwise, more surprisingly, acquisition incentives turn out insufficient even under voluntary disclosure for an informational setting referred to as selfish acquisition. For another setting, referred to as cooperative acquisition, the incentives under voluntary disclosure are even lower as compared with mandatory disclosure. All results hold independently of the underlying bargaining structure and equilibrium selection as exclusive use of constraints is made that hold for equilibrium payoffs from any bargaining game.
Keywords: K12; C72; D82; 330